2017
DOI: 10.1002/mnfr.201700674
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐Rich Apple Improves Endothelial Function in Individuals at Risk for Cardiovascular Disease: A Randomized Controlled Clinical Trial

Abstract: A lower risk of CVD with higher apple consumption could be mediated by the beneficial effect of apple skin on endothelial function, both acutely and chronically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 47 publications
0
60
1
Order By: Relevance
“…Citrus species are natural products and notably rich in flavonoid compounds which are famous for multiple therapeutic benefits. Citrus flavonoids have been researching in recent years underlying its beneficial activities such as antioxidation, anti-inflammation, and anti-cardiovascular diseases (Bondonno et al, 2018;Vazhappilly et al, 2019). Additionally, some clinical trials found that plant flavonoids are effective in preventing obesity, type 2 diabetes, and some metabolic syndromes (Guo et al, 2016;Pan et al, 2017), which are strongly associated with NASH.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus species are natural products and notably rich in flavonoid compounds which are famous for multiple therapeutic benefits. Citrus flavonoids have been researching in recent years underlying its beneficial activities such as antioxidation, anti-inflammation, and anti-cardiovascular diseases (Bondonno et al, 2018;Vazhappilly et al, 2019). Additionally, some clinical trials found that plant flavonoids are effective in preventing obesity, type 2 diabetes, and some metabolic syndromes (Guo et al, 2016;Pan et al, 2017), which are strongly associated with NASH.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled clinical study was done on flavonoid-rich Cripps Pink apple skins with individuals who are at risk for CVD to improve endothelial function [13]. Due to this randomized controlled clinical study, the term flavonoids are used instead of polyphenols and will be used only for this section of the review.…”
Section: Endothelial and Arterial Functionmentioning
confidence: 99%
“…In another study by Croft et al (2017), the Hmox1 induction effects of 9 purified flavonoids (5 unmetabolized flavonoids and 4 metabolites) in HAECs were comparatively scrutinized. Quercetin, rather than its methyl or sulfate metabolites, presented excellent induction effects on Hmox1 at physiologically relevant concentrations (from 5 to 10 lM).…”
Section: Induction Of Antioxidant Enzymesmentioning
confidence: 99%
“…Endothelial dysfunction occurs early in the pathological process of atherosclerosis, and is an independent predictor of cardiovascular disease. Over last two decades, numerous intervention studies with certain flavonoids (Bondonno et al, ; Loke et al, ; Schroeter et al, ) or foods rich in flavonoids (Agewall et al, ; Bondonno et al, ; Nakayama, Tsuge, Sawada, & Higashi, ) have shown improvements in cardiovascular risk factors such as endothelial function. Additionally, the potential protective effects of different flavonoids on vascular endothelial function are probably dependent on their structural properties (Hooper et al, ).…”
Section: Introductionmentioning
confidence: 99%